2014
DOI: 10.3889/oamjms.2014.059
|View full text |Cite
|
Sign up to set email alerts
|

The Most Common New Cases of Breast Cancer among the Housewives: The Some Carcinogenic Determinants

Abstract: BACKGROUND: Numerous studies have observed risk factors for breast cancer. We aimed to investigate and assess the relationship between individual, social, occupational and environmental determinants of breast cancer using a questionnaire among 100 newly diagnosed female breast cancer patients and 100 control female subjects without cancer.METHODS: A case-control study using a family ambulatory based survey was conducted among 200 female patients from all municipalities of Zenica - Doboj Canton. New cases of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(41 reference statements)
0
3
0
1
Order By: Relevance
“…Several studies have shown an increase in the incidence of breast cancer in women exposed to the main ingredients of the chemical industry such as polycyclic aromatic hydrocarbons (PAH), some solvents, pesticide ingredients, and metals (Engel & Rasanayagam, 2015;Fenga, 2016;International Agency for Research and Cancer & World Health Organization, 2012). Besides, the risk of breast cancer is also found in women who work in the pharmaceutical, cosmetics, hairdresser, radiation/x-ray machine, cleaning products, car operators, and so on (Brophy et al, 2006;Engel & Rasanayagam, 2015;Ji et al, 2008;Pranjić et al, 2015). Therefore, every worker who may be potentially exposed to carcinogenic materials must determine how to protect themselves with appropriate engineering and administrative controls, safe work practices, and personal protective equipment (International Labour Organization, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown an increase in the incidence of breast cancer in women exposed to the main ingredients of the chemical industry such as polycyclic aromatic hydrocarbons (PAH), some solvents, pesticide ingredients, and metals (Engel & Rasanayagam, 2015;Fenga, 2016;International Agency for Research and Cancer & World Health Organization, 2012). Besides, the risk of breast cancer is also found in women who work in the pharmaceutical, cosmetics, hairdresser, radiation/x-ray machine, cleaning products, car operators, and so on (Brophy et al, 2006;Engel & Rasanayagam, 2015;Ji et al, 2008;Pranjić et al, 2015). Therefore, every worker who may be potentially exposed to carcinogenic materials must determine how to protect themselves with appropriate engineering and administrative controls, safe work practices, and personal protective equipment (International Labour Organization, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is not common in younger women (less than 20 years) and older women (more than 80 years) (Autier et al, 2010). Other studies found that women 45 years of age and older are at high risk of suffering from breast cancer (Pranjić et al, 2015). Several factors are believed to influence such as geographical location (solar ultraviolet exposure), early age of menarche (under 12 years), low parity, lactation, obesity, genetics, and the family history of breast cancer (Laden & Hunter, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pertumbuhan risiko kanker payudara juga diamati pada wanita yang dipekerjakan di industri farmasi, produksi kosmetik, penata rambut, perawat, teknisi laboratorium, ahli kebersihan gigi dan produksi mobil. (Pranjic et al, 2014) Penelitian sebelumnya di Italia mengungkap mengenai hubungan antara kerja shift malam dan morbiditas kanker payudara. Paparan cahaya di malam hari dapat menekan puncak produksi melatonin dan jam sirkadian utama, mengakibatkan terjadinya gangguan tidur yang dapat memberi efek negatif pada sistem kekebalan tubuh.…”
Section: Hubungan Pekerjaan Dengan Fenotipe Molekuler Her-2unclassified